A real time method for surface cleanliness measurement - Bilmes, Gabriel Mario (2006)
The measurement of surface cleanliness is a signifi cant problem in many industrial and technological processes. Existing methods are based on laboratory procedures, that are not performed in real time, can not be automated, and usually are restricted to a small portion of the sample. In this study we describe a new method for real time measurement of the amount of surface dirt or contamination deposited on a surface. It relies on the ablation of the surface dirt film by means of a short laser pulse, and the subsequent measurement of the emitted sound. The intensity of the sound is proportional to the amount of surface dirt and provides a direct measurement of the cleanli ness of the surface. We also developed a reference sample for calibration, based on a uniform distribution of dots printed on white paper. The density and the dot size can be easily modified providing a homogeneous, uniform and reproducible standard for the measurement. Based on this method, we designed, de veloped and patented the first industrial instrument for on line determination of the degree of cleanliness of manufactured cold rolled steel plate bobbins.